2020
DOI: 10.1007/s00415-020-10366-9
|View full text |Cite
|
Sign up to set email alerts
|

Portable fixed dynamometry: towards remote muscle strength measurements in patients with motor neuron disease

Abstract: Background We aimed to determine (1) the test–retest reliability of a newly developed portable fixed dynamometer (PFD) as compared to the hand-held dynamometer (HHD) in patients with motor neuron disease (MND) and (2) the PFD’s ability to reduce possible examiner-induced ceiling effects. Methods Test–retest reliability of isometric muscle strength of the quadriceps was measured in patients with MND and non-neurological controls using the HHD and PFD. Relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…All of the CNSDs mentioned above share disabling symptoms such as difficulties in voluntary extremity movement [5], gait and balance disorders [6], and decreased functional capacity and personal autonomy [7]. The most common disabling alterations in CNSDs are motor impairments in the upper extremities (UE) that reduce the range of motion (ROM) [8] and produce muscle weakness and/or spasticity [9]. In addition, Smeragliuolo et al [46] reported that the LMC is accurate for wrist flexion/extension and radial and cubital deviation, although it is less precise for arm supination and pronation.…”
Section: Introductionmentioning
confidence: 99%
“…All of the CNSDs mentioned above share disabling symptoms such as difficulties in voluntary extremity movement [5], gait and balance disorders [6], and decreased functional capacity and personal autonomy [7]. The most common disabling alterations in CNSDs are motor impairments in the upper extremities (UE) that reduce the range of motion (ROM) [8] and produce muscle weakness and/or spasticity [9]. In addition, Smeragliuolo et al [46] reported that the LMC is accurate for wrist flexion/extension and radial and cubital deviation, although it is less precise for arm supination and pronation.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical impedance myography, which works through the application of low-intensity electrical currents to the muscles, was shown to be potentially suitable to evaluate MND progression [ 31 ]. Two studies explored the use of fixed and portable dynamometry devices to assess global and precise muscle strength [ 16 , 21 ], with hand-held dynamometry devices a common comparison measure to establish the suitability of new exploratory devices [ 12 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a new portable fixed dynamometry was developed to assess quadriceps muscle strength in patients with motor neuron diseases [50], showing much higher reliability compared to the classic HHDs. This tool, composed of two HHDs fixated in a rigid framework, helps to reduce the effect of the examiner's strength and may be applied in a home setting.…”
Section: Resultsmentioning
confidence: 99%